The development of a social, demographic and land use profiler for areas of high crime - Hirschfield, Alex (The British journal of criminology, 1997)
Maps that show the patterns of crimes do not allow the investigator to analyse, in depth, the relationships between levels of crime and the social and physical environment. In order to address these shortcomings, a demographic, land use and crime risk profiling system has been developed and piloted on Merseyside. This paper sets out the need for a profiling system, discusses the data sets which are used and addresses a number of issues concerning profile production and design. The paper concludes with a series of examples showing different applications of the profiler and describes an agenda for future research